Thrombospondins in the Transition from Myocardial Infarction to Heart Failure - Kirk, Jonathan A. (J Mol Cell Cardiol, 2015)
The heart’s reaction to ischemic injury from a myocardial infarction involves complicated cross-talk between the extra-cellular matrix (ECM) and many different cell types within the myocardium. The ECM functions not only as a scaffold where myocytes beat synchronously, but an active signaling environment that regulates the important post-MI responses. The thrombospondins are matricellular proteins that modulate cell - ECM interactions, functioning as “sensors” that mediate outside-in and inside-out signaling. Thrombospondins are highly expressed during embryonic stages, and although their levels decrease during adult life, can be re-expressed in high quantities in response to cardiac stress including myocardial infarction and heart failure. Like a swiss-army knife, the thrombospondins possess many tools: numerous binding domains that allow them to interact with other elements of the ECM, cell surface receptors, and signaling molecules. It is through these that the thrombospondins function. In the present review, we provide basic as well as clinical evidence linking the thrombospondin proteins with the post myocardial infarction response, including inflammation, fibrotic matrix remodeling, angiogenesis, as well as myocyte hypertrophy, apoptosis, and contractile dysfunction in heart failure. We will describe what is known regarding the intracellular signaling pathways that are involved with these responses, paving the road for future studies identifying these proteins as novel therapeutic targets for cardiac disease.